Response of Turkey Growers Fed Fermented Shea Butter Cake Based Diets with Fullzyme® Supplementation (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
A 6-week experiment was conducted to evaluate the growth performance and economic analysis of broad breasted bronze turkey growers fed diets containing fermented shea butter cake meal (FSBCM) as replacement for maize with Fullzyme® supplementation. Three treatment diets were formulated, where T1 contained maize-soybean based control diet, T2 had 25% FSBCM replacing maize in T1 diet and T3 contained 0.5% Fullzyme supplementation to T2 diet. A total of 72, six-week old unsexed broad breasted bronze turkey growers were weighed and allocated to three dietary treatments with four replications of six birds each in a completely randomized design (CRD). Data collected on feed intake, body weight gain and feed:gain as well as cost indices were subjected to analysis of variance with the aid of SAS software package. Feed and water were provided ad libitum. Results showed that significant (P
Keywords: Multienzymes; Performance; Probiotic; Shea butter cake; Turkey